Emerging Spectrum of Perforation Peritonitis in Developing World - Hameed, Tariq; Kumar, Awadh; Sahni, Shivanand; Bhatia, Rahul; Vidhyarthy, Ajit Kumar (Frontiers in Surgery, 2020)
Background: Gastrointestinal perforations constitute a major cause of patients with acute abdomen pain coming to the surgery emergency room. Incidence, site of perforation, and age is different in the developing world and is showing new trends. The etiological spectrum in the developing world is different from the western world. This study was conducted to find out the latest trends in perforation peritonitis in India. Methods: This study was conducted in a single surgical unit of Darbhanga Medical College and Hospital, India. A total of 350 consecutive patients with perforation peritonitis were studied in terms of age, sex, seasonal variation, biochemical parameters, clinical presentation, radiological and intraoperative findings, surgical intervention, and postoperative outcome. Results: The most common cause of perforation peritonitis in our study was a duodenal ulcer ( 50%) followed by typhoid (20%), traumatic (14.5%), appendicular (7.4%), and tubercular (3.1%) cases. Males were three times more commonly affected than females. Peak incidence was noted in the 2nd and 3rd decades of life. Peptic ulcer perforations were common in autumn and winter and typhoid perforations were common during the summer and rainy seasons. Conclusion: Spectrum of perforation peritonitis cases in this part of world is different from developed western countries. It is different in respect of younger age at presentation, site of perforation, and etiological factors. Infective pathology makes up to a quarter of total cases in the developing world. The developing world has more perforation peritonitis cases involving the upper gastrointestinal tract, while the western world has a predominance of lower gastrointestinal tract perforations.